Disarming Cellular Alarm Systems—Manipulation of Stress-Induced NKG2D Ligands by Human Herpesviruses - Schmiedel, Dominik; Mandelboim, Ofer (Frontiers in Immunology, 2017)
The co-evolution of viruses and their hosts led to the repeated emergence of cellular alert signals and viral strategies to counteract them. The herpesvirus family of viruses displays the most sophisticated repertoire of immune escape mechanisms enabling infected cells to evade immune recognition and thereby maintain infection. The herpesvirus family consists of nine viruses that are capable of infecting humans: Herpes Simplex Virus 1 and 2 (HSV-1, HSV-2), Varicella Zoster Virus (VZV), Epstein-Barr-Virus (EBV), Human Cytomegalovirus (HCMV), Roseoloviruses (HHV-6A, HHV-6B and HHV-7) and Kaposi’s-sarcoma-associated Herpesvirus (KSHV). Most of these viruses are highly prevalent and infect a vast majority of the human population worldwide. Notably, research over the past 15 years has revealed that cellular ligands for the activating receptor NKG2D – which is primarily expressed on natural killer (NK) cells – are common targets suppressed during viral infection, i.e. their surface expression is reduced in virtually all lytic herpesvirus infections by diverse mechanisms. Here, we review the viral mechanisms by which all herpesviruses known to date to down-modulate the expression of the NKG2D ligands. Also, in light of recent findings, we speculate about the importance of the emergence of eight different NKG2D ligands in humans and further allelic diversification during host and virus co-evolution.